Development and characterization of 33 novel polymorphic microsatellite markers for the brown tree snake Boiga irregularis. (December 2015) - Unger, Shem; Abernethy, Erin; Lance, Stacey; Beasley, Rochelle; Kimball, Bruce; McAuliffe, Thomas; Jones, Kenneth; Rhodes, Olin
Abstract Background Boiga irregularis is a widespread invasive species on Guam and has led to extirpation of most of the island's native avifauna. There are presently no microsatellite markers for this invasive species, hence we developed highly polymorphic microsatellite markers to allow for robust population genetic studies on Guam. Findings We isolated and characterized 33 microsatellite loci for the brown tree snake, B. irregularis . The loci were screened across 32 individuals from Guam. The number of alleles per locus ranged from three to ten, with an average of 4.62. The expected (He ) and observed heterozygosity (Ho ) ranged from 0.294 to 0.856 and from 0.031 to 0.813, with an average of 0.648 and 0.524, respectively. Significant deviations from Hardy–Weinberg equilibrium were detected at seven loci after Bonferoni correction. Probability of identity values ranged from 0.043 to 0.539. Conclusions These genetic markers are useful for understanding a suite of post-invasion population genetic parameters, sources of invasions, and effectiveness of management strategies for this invasive species.